2009
DOI: 10.1186/1471-2407-9-449
|View full text |Cite
|
Sign up to set email alerts
|

Compound K, a metabolite of ginseng saponin, induces apoptosis via caspase-8-dependent pathway in HL-60 human leukemia cells

Abstract: BackgroundCompound K [20-O-β-(D-glucopyranosyl)-20(S)-protopanaxadiol], a metabolite of the protopanaxadiol-type saponins of Panax ginseng C.A. Meyer, has been reported to possess anti-tumor properties to inhibit angiogenesis and to induce tumor apoptosis. In the present study, we investigated the effect of Compound K on apoptosis and explored the underlying mechanisms involved in HL-60 human leukemia cells.MethodsWe examined the effect of Compound K on the viabilities of various cancer cell lines using MTT as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 43 publications
3
69
0
Order By: Relevance
“…As one of the primary pathways of apoptosis, a mitochondria pathway, which is controlled through the bcl-2 family of proteins, is activated, and is finalized when caspase-3, a final executing factor, and DNase is activated, resulting in apoptosis by DNA fragmentation and the formation of apoptotic bodies. 23) In this study, we found that inactive caspase-3 protein decreased in a time-dependent manner in cells treated with the EtOAc fraction, while active caspase-3 protein increased in a time-dependent manner. Also, the expression of active caspase-3 protein was significantly abrogated in the presence of the pan-caspase inhibitor Z-VAD-FMK, indicating the EtOAc fraction induces apoptosis of AGS cells by a caspase-3 dependent mechanism.…”
Section: Discussionsupporting
confidence: 47%
“…As one of the primary pathways of apoptosis, a mitochondria pathway, which is controlled through the bcl-2 family of proteins, is activated, and is finalized when caspase-3, a final executing factor, and DNase is activated, resulting in apoptosis by DNA fragmentation and the formation of apoptotic bodies. 23) In this study, we found that inactive caspase-3 protein decreased in a time-dependent manner in cells treated with the EtOAc fraction, while active caspase-3 protein increased in a time-dependent manner. Also, the expression of active caspase-3 protein was significantly abrogated in the presence of the pan-caspase inhibitor Z-VAD-FMK, indicating the EtOAc fraction induces apoptosis of AGS cells by a caspase-3 dependent mechanism.…”
Section: Discussionsupporting
confidence: 47%
“…Ginsenosides, the major components of ginseng, exhibit various biological activities, including anti-inflammatory, anti-dementia, and anti-tumor effects [17][18][19] . The protopanaxadiol ginsenosides Rb1, Rb2, and Rc are metabolized to compound K (C-K; Figure 1) by intestinal bacteria in humans and rats [20][21][22] . C-K (20-O-β-D-glucopyranosyl-20(S)-protopanaxadiol) exhibits various immunopharmacological properties, including antiallergic and anti-carcinogenic effects [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…The major active components of ginseng are ginsenosides (such as Rg3, Rh2, Rg5, Rk1 and Rp1), a diverse group of steroidal saponins (12,13). Although the anti-tumor activities of ginseng were initially attributed to its immunomodulation activities (12), it has been reported that ginseng or ginsenosides may exhibit direct anti-cancer properties (14)(15)(16)(17)(18). Several ginsenosides (e.g., Rh2, Rg3, and Rk1) exhibit anti-proliferative and antiangiogenic activities in vitro and in vivo (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%